Clinical significance of Janus Kinase inhibitor selectivity - Choy, Ernest H (Rheumatology (Oxford, England), 2019)
Cytokines are key drivers of inflammation in RA, and anti-cytokine therapy has improved the outcome of RA. Janus Kinases (JAK) are intracellular tyrosine kinases linked to intracellular domains of many cytokine receptors. There are four JAK isoforms: JAK1, JAK2, JAK3 and TYK2. Different cytokine receptor families utilize specific JAK isoforms for signal transduction. Phosphorylation of JAK when cytokine binds to its cognate receptor leads to phosphorylation of other intracellular molecules that eventually leads to gene transcription. Oral JAK inhibitors (JAKi) have been developed as anti-cytokine therapy in RA. Two JAKi, tofacitinib and baricitinib, have been approved recently for the treatment of RA, and many JAKi are currently in development. JAKi inhibit JAK isoforms with different selectivity. This review discusses the efficacy and safety of JAKi in RA, in particular the potential clinical significance of JAKi selectivity.